PENGARUH BUANGAN LIMBAH CAIR PABRIK KELAPA SAWIT TERHADAP KUALITAS AIR SUNGAI MABAT KABUPATEN BANGKA - SITI ZAHARA; UMROH UMROH; EVA UTAMI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2016)
Mabat river is upstream watershed Baturusa which has a length of 15 km. Mabat river utilized for bathing, washing and fishing. Utilization Mabat River is no longer optimal due to the effect of effluent disposal plant oil palm. The purpose of this study was to analyze the quality of the Mabat river water of the effluent disposal plant oil palm. This study was conducted in February 2016 in Mabat river, Bangka District. Data retrieval consists of four stations. Station 1 on rivers that have not been exposed to effluent disposal palm. Stations 2, 3 and 4 on the river that has been exposed to effluent disposal palm. Methods of data analysis used the Pollutant Index method. The results obtained in the analysis of the sample is then compared with the first class water quality standards based on Government Regulation number 82 of 2001. Station 1, 2, 3 and 4 show the status of water in blackened mild conditions with the value of each 1,554; 1,802; 2,136 and 2,675.